Critical Review of Innovations in Healthcare Delivery: Addressing Efficiency, Patient-Centered Care, And Global Health - Aldhumayri, Mohammed Sami M; Aldaghmani, Yazeed Farhan; Alruwaili, Mari Muteb M; Alalyan, Salma Fahhad Salem; Alrwailiy, Kholod Moadeb Marzoq; Alrwaili, Ashwag Eid Nahi; Alruili, Abdulsalam Ruished K; Alshigi, Mohammed Abdulrahman Mohammed; Alotaibi, Saad Abdullah; Alhakami, Badriah Ibrahim (Journal of Ecohumanism, 2024)
This critical review evaluates the innovations in healthcare delivery, focusing on three main aspects: healthcare costs, organization, patient, and international. Due to increased pressure on healthcare systems globally through high costs, aging citizens, and the prevalence of conditions requiring long-term attention, new care delivery and technology have been found to contain these challenges. This paper focuses on various trends, including Digital health, Telemedicine, artificial intelligence in healthcare, Value-based care, and Universal Health Coverage. The review evaluates these innovations regarding organizational effectiveness, patient satisfaction, and impact on advancing global health. In this paper, I provide a brief literature review describing the specific details of these innovations and their limitations and accomplishments. The future directions include further development of such innovations, tackling current challenges, and fostering international cooperation.